Managing cooperatives for sustainability in the Community Work Programme (CWP) - Dichabe, Barileng Bathakgile (My University, 2015)
The purpose of the research was to uncover reasons why poverty alleviation initiatives have not yet yielded satisfactory sustainable development in the country. The non-sustainability of cooperatives has been a challenge within poverty alleviations programmes. Government has initiated various poverty alleviation programmes in an effort to fight poverty, however, some of these projects emanating from these poverty alleviation initiatives have not been sustainable and end up collapsing, this has affected the lives of people who have become solely reliant on them as a means of income generation. This matter has also been outlined in the Fifteen Year Review Report of Income Poverty Alleviation Programmes in Social and Related Sectors in 2008, stating that early weaknesses in M&E, the inability to demonstrate “community driving” and cost inefficiency are partly to blame for the failure of poverty alleviation programmes. In 2004, the then President, Thabo Mbeki, outlined three pillars as a Government strategy to fight under development and poverty in the country (www.psc.gov.za, Report on an audit of Government’s Poverty Reduction Programmes and Projects:2007:10-16). Those pillars were: · Enlarge growth and development in the first economy · Increase the possibility to create jobs and address challenges of the second economy · Build a social security net to bring about poverty alleviation. The above report further indicates various programmes earmarked to fight poverty such as the Expanded Public Works Programme (EPWP); Integrated Sustainable Rural Development Programme (ISRDP); Urban v | P a g e Renewal Programme (URP); Local Economic Development (LED); Municipal Infrastructure Grant (MIG) etc. This indicates concerted efforts by Government to fight poverty and underdevelopment which is necessary to bring about sustainable development. The results of the study clearly indicate gaps in intergovernmental support to the community work programme. The cooperatives linked with the programme clearly require a multi-departmental support such as funding, training, monitoring, support from the Department of Cooperative Governance; Seedlings and skills from Department of Agriculture; Land to plough or use for recycling from the Municipality/tribal authority/ Department of Land Affairs; Access to market their produce/wares from the Department of Trade and Industry/ Tshwane Municipality etc. There should be legislation mandating all relevant departments to consolidate efforts to provide support and guidance to specific cooperatives.
Thesis (M.M.)--University of the Witwatersrand, Faculty of Commerce, Law and Management, Graduate School of Public and Development Management, 2015